The social brain: psychological underpinnings and implications for the structure of organizations - Dunbar, R (SAGE Publications, 2014)
The social-brain hypothesis refers to a quantitative relationship between social-group size and neocortex volume in monkeys and apes. This relationship predicts a group size of approximately 150 for humans, which turns out to be the typical size of both social communities in small-scale societies and personal social networks in the modern world. This constraint on the size of social groups is partly cognitive and partly temporal. It gives rise to a layered structure in primate and human social groups that, in humans, reflects both emotional closeness in relationships and the frequency of contact. These findings have potentially important implications for the way in which human organizations are structured.